2015
DOI: 10.1002/jbm.b.33349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle size and porosity on in vivo remodeling of settable allograft bone/polymer composites

Abstract: Established clinical approaches to treat bone voids include the implantation of autograft or allograft bone, ceramics, and other bone void fillers (BVFs). Composites prepared from lysine-derived polyurethanes and allograft bone can be injected as a reactive liquid and set to yield BVFs with mechanical strength comparable to trabecular bone. In this study, we investigated the effects of porosity, allograft particle size, and matrix mineralization on remodeling of injectable and settable allograft/polymer compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 36 publications
6
40
0
Order By: Relevance
“…The primary outcome was bone volume/total volume measured by lCT in the middle region of the defect. An a priori power analysis indicated that a sample size of four would detect a 7.5% difference in bone volume/total volume between groups assuming a mean and SD of 30% and 5%, respectively in the middle region of interest of the graft (2.5 mm from the center-line) [13,37]. This is with a power of 80% and an alpha level of 0.05 using a two-tailed t-test of two independent samples.…”
Section: Biofilm Inhibition and Dispersal Assaysmentioning
confidence: 99%
See 4 more Smart Citations
“…The primary outcome was bone volume/total volume measured by lCT in the middle region of the defect. An a priori power analysis indicated that a sample size of four would detect a 7.5% difference in bone volume/total volume between groups assuming a mean and SD of 30% and 5%, respectively in the middle region of interest of the graft (2.5 mm from the center-line) [13,37]. This is with a power of 80% and an alpha level of 0.05 using a two-tailed t-test of two independent samples.…”
Section: Biofilm Inhibition and Dispersal Assaysmentioning
confidence: 99%
“…Osteoclast precursor cells were prepared from spleens of four adult C57 WT mice by the Ficoll (Lymphocyte Separation Medium; MP Biomedicals, Solon, OH, USA) gradient method [6] and plated separately at a density of 2. [13,14,37]. An advantage of low-viscosity grafts compared with calcium phosphate cements or allograft is its ability to support diffusion-controlled sustained release of biologics [20,41].…”
Section: Biofilm Inhibition and Dispersal Assaysmentioning
confidence: 99%
See 3 more Smart Citations